Evaluation of Activated Carbon Electrodes as Anodes in a Microbial Fuel Cell Using Shewanella Putrefaciens (2020)
In this work, three types of activated carbons were evaluated as electrodes in the anode chamber of a two-chamber microbial fuel cell (MFC). The evaluation was applied using a pure Shewanella Putrefaciens culture due to its gram-negative characteristics. In the cathode chamber, a platinum electrode was used, and a Nafion® 117 proton exchange membrane was selected as a separator of both chambers. The activated carbons were obtained from different precursors (coffee husk, commercial coal, and mineral coal), with different microporous and surface properties. From the voltage and current measurements, it was found that the cell power values ​​varied between 0.008 mW and 0.045 mW. The electrode obtained from chemical activation of coffee husk with H3PO4 at 450 °C (Q) showed the best electrochemical behaviour and highest power values. This result may be mainly related to the macroscopic morphology and mesopores that improve the wettability of the surface by the medium thought carbonaceous material. SEM images showed a better biofilm formation, larger filaments of the bacteria, and micro-beds formation over the surface of bio-anode Q, which improved the interaction with the microorganism, its metabolism, and electrons extracellular transfer. Therefore, activated carbon from coffee husk could be considered as a promising material for electrodes of microbial fuel cells.